Decomposition of Poland's Bilateral Trade Imbalances by Value Added Content - Łukasz Ambroziak (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is to present differences in Poland’s bilateral trade balances in gross terms and in value added terms in 1995-2011, as well as an explanation of such differences.